Current status of the thyroid hormone measurement items in patients receiving levothyroxine monotherapy by the management based on the thyroid tissue volume - Mitsuru Ito; Hanna Deguchi-Horiuchi; Sawako Takahashi; Mako Hisakado; Kazuyoshi Kohsaka; Eijun Nishihara; Shuji Fukata; Mitsushige Nishikawa; Akira Miyauchi; Takashi Akamizu (Endocrine Journal)
We and other investigators reported that mild TSH suppression with levothyroxine (LT4) was needed to achieve normal free triiodothyronine (FT3) levels and metabolic euthyroid state in athyreotic patients. Consequently, management methods based on thyroid tissue volume have been implemented for patients receiving LT4 at the Kuma Hospital. This retrospective study examined the composition of the thyroid hormone measurement items (serum-free thyroxine [FT4], FT3, and FT4 + FT3) in patients receiving LT4 monotherapy. According to the etiology of hypothyroidism, 36% of the 25,523 patients included in this study underwent total thyroidectomy (TT). Thirteen percent and 14% had undergone 131I treatment for hyperthyroidism (RIT) and partial thyroidectomy (PT), respectively. Moreover, 37% of patients had received non-invasive treatment (NIT). The proportion of patients who underwent only FT3 measurements was higher (TT, 93%; RIT, 61%) in the first two groups, whereas the proportion of patients who underwent only FT4 measurements was higher (PT, 50%; NIT, 65%) in the remaining two groups. Only FT3 measurements were performed in 58% of patients. Only FT4 measurements were performed in 34% of patients. The serum TSH levels were suppressed in nearly half of the patients (46%). Thus, FT3 was the major thyroid hormone measured in patients receiving LT4 treatment, and the serum TSH levels were suppressed in nearly half of the patients. This may be attributed to the management guidelines at our hospital, a specialized facility for thyroid disease, wherein half of the patients present are athyreotic or have atrophic thyroid glands after TT or RIT.